An examination of how organisational policy and news professionalism are negotiated in a newsroom: a case study of Zimbabwe's Financial gazette - Gandari, Jonathan (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2010)
The construction of journalistic professionalism in Zimbabwe has stirred debate among scholars. Critics have argued that professionalism has been compromised by the stifling media laws in Zimbabwe as well as the extra legal measures the state has enforced to control the press. Some have also argued that a new kind of journalism must be emerging in the Zimbabwean newsroom as journalism try to cope with the political and economic pressures bedeviling the country. Much of this criticism however, has not been based on close interrogation of professionalism from the perspective of the journalists in any particular newsroom. It is against this background that this study examines the constructions of professionalism at the Financial Gazette. In particular it explores the meaning of professionalism through interrogating the journalistic practices the journalists consider during the process of news production in the context of overwhelming state power. In undertaking this examination, the study draws primarily on qualitative research methods, particularly observation and multi-layered individual in-depth interviews. As the study demonstrates, the interrogation of professionalism from the perspective of newsroom practices uncovers the complex manner in which professionalism is negotiated in the Gazette's newsroom located in a country undergoing transition in Democracy. The study establishes that when measured against normative canons of journalistic professionalism the Gazette is deviating from such tenets as public service and watchdog journalism. As the study indicates, perhaps unbeknown to the respondents, the ruling ZANU PF party hegemony is reproduced at the Gazette through choice of news values such as sovereignty and patriotism all euphemisms for ruling party's slogans.
Keywords: Financial gazette Journalism -- Zimbabwe; Journalism -- Political aspects -- Zimbabwe; Journalistic ethics; Journalists -- Zimbabwe; Newspapers -- Zimbabwe; Mass media -- Political aspects -- Zimbabwe; Mass media -- Law and legislation -- Zimbabwe